The Burghal Hidage and the West Saxon burhs: a reappraisal. (24th July 2017) - Haslam, Jeremy
Abstract: This article examines new evidence and arguments relating to the political, strategic and historical context of the Burghal Hidage document and the burhs which it lists. This evidence can be best interpreted by reference to the thesis that the Burghal Hidage was a near-contemporary record of a complete system of burhs which gave King Alfred political and strategic control of the full extent of the West Saxon kingdom on both sides of the river Thames at a particular period. The burhs are seen as the instruments through which the submission of the populations of their associated territories to the king's lordship was consolidated. As such, their formation as a system is uniquely appropriate to the political and strategic circumstances obtaining in the late 870s. A possible context for the document is suggested as being the surviving 'boundary' section of a longer 'charter of submission', issued by King Alfred in the context of the affirmation of his re-established hegemony of the Kingdom of the West Saxons in the period 878–9.